Influence of the Grain-Flow Orientation after Hot Forging Process Evaluated through Rotational Flexing Fatigue Test - Jaques Araripe Suris; Charles Chemale Yurgel; Ricardo Alves de Sousa (Metals, 2023)
The hot forging process brings significant advantages in terms of improved mechanical properties of the part compared with other processes, such as casting or machining. The metal flow in the forging process leads to texture modifications and can be macroscopically visualized by the so-called grain-flow orientation (GFO). This study showed the effect of GFO on fatigue life by using a rotational flexing fatigue test. The tests that were performed using SAE 1045H steel material, at rolling and transverse directions, showed the influence of GFO on the specimens’ mechanical properties compared with the reference samples taken from the machined rolled bar. The experimental results showed that the forged samples with the GFO in the main deformation direction presented a higher fatigue life than the other tested configurations.